Perancangan dan Implementasi Aplikasi Pemindaian Port Berbasis GUI (Bryan Scan) Sebagai Alat Bantu Analisis Keamanan Jaringan: Rekayasa Keamanan Siber - mohammadsudi sudi; Muhamad Ridwan; Asep Suryanta (Pustaka Poltekad, 2026)
The increasing complexity of computer network infrastructures requires a systematic and user-friendly security auditing mechanism. One of the essential stages in network security auditing is port scanning, which is used to identify active services that may pose potential security vulnerabilities. However, most tools such as Nmap are still based on a Command Line Interface (CLI), requiring technical expertise to interpret the scanning results effectively.This study aims to design and implement a Graphical User Interface (GUI)-based port scanning application named Bryan Scan, which integrates the Nmap engine as a supporting tool for network security analysis. The research method employs the System Development Life Cycle (SDLC) Waterfall model, consisting of requirements analysis, system design, implementation, testing, and evaluation stages. The system is developed using Python, integrating Nmap through system calls and processing XML-based output.The results indicate that Bryan Scan is capable of displaying open ports, active services, operating system detection, and automatically generating a rule-based security risk score. The level of conformity between Bryan Scan and Nmap CLI reaches ≥95%, with improved ease of analysis based on usability testing results. Therefore, the application is feasible to be utilized as a structured and informative tool for internal network security auditing.